INTEGRASI PENILAIAN FORMATIF PADA PEMBELAJARAN MICROTEACHING DI PRODI PENDIDIKAN MATEMATIKA UNIVERSITAS QOMARUDDIN - Illah Winiati Triyana; Junaidah Wildani (Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to integrate formative assessment into microteaching course and to know students’ response toward the integration of formative assessment into microteaching course. To achieve these goals, the researcher applied pra-experimental research design in the type of one-shot case study with the subject of this study is students from mathematics education study program in semester six 2019-2020 academic year. The instrument used to collect the data for is student questioner which has been validated by two experts. The result of data analysis shows that formative assessment has been very well integrated to microteaching learning and 100% students agreed and very agreed that formative assessment helps them in knowing what to do to achieve their knowledge and skill target. 95,85% students agreed and very agreed that formative assessment helps them in knowing their knowledge and skill target. 93,75% students agreed and very agreed that through the integration of formative assessment, they are motivated to improve their knowledge and skill. 93,7% students agreed and very agreed that formative assessment helps them knowing what they know and what they skilled. 91,68% students agreed and very agreed that through integration of formative assessment they become independent learners.